2010
DOI: 10.1158/0008-5472.can-10-0847
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3B7, a Truncated DNMT3B Isoform Expressed in Human Tumors, Disrupts Embryonic Development and Accelerates Lymphomagenesis

Abstract: Epigenetic changes are among the most common alterations observed in cancer cells, yet the mechanism by which cancer cells acquire and maintain abnormal DNA methylation patterns is not understood. Cancer cells have an altered distribution of DNA methylation and express aberrant DNA methyltransferase 3B transcripts, which encode truncated proteins, some of which lack the COOH-terminal catalytic domain. To test if a truncated DNMT3B isoform disrupts DNA methylation in vivo, we constructed two lines of transgenic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 40 publications
10
73
0
Order By: Relevance
“…A separate study in Eµ-Myc mice demonstrated a modest increase in DNA methylation by transgenic expression of DNMT3B7, a truncated isoform of DNA methyltransferase 3B that has been found in human cancer cells. 32 This finding is not cancer-specific, however, since an increase in promoter CpG island DNA methylation was observed by ectopic expression of mouse Dnmt3b in normal mouse colon cells. 33 Mouse cells are capable of obtaining extensive promoter CpG island DNA hypermethylation when they are immortalized, as recently shown 29 and in this study.…”
Section: Discussionmentioning
confidence: 90%
“…A separate study in Eµ-Myc mice demonstrated a modest increase in DNA methylation by transgenic expression of DNMT3B7, a truncated isoform of DNA methyltransferase 3B that has been found in human cancer cells. 32 This finding is not cancer-specific, however, since an increase in promoter CpG island DNA methylation was observed by ectopic expression of mouse Dnmt3b in normal mouse colon cells. 33 Mouse cells are capable of obtaining extensive promoter CpG island DNA hypermethylation when they are immortalized, as recently shown 29 and in this study.…”
Section: Discussionmentioning
confidence: 90%
“…26,27 DNMT3b is directly associated with many human diseases including cancer. 28,29 For example, upregulation of DNMT3b expression is observed in sporadic breast carcinoma and acute myeloid leukemia while DNMT1 and DNMT3a levels are reduced. 30 DNMT3b is also overexpressed and linked to the CpG island methylator phenotype in colon cancer.…”
Section: Correlation Of Ereg Promoter Methylation With Transcriptionamentioning
confidence: 99%
“…In the study mentioned previously, Ostler and colleagues noted the presence of DNMT3B7 in several different cancer cell lines [14] . Shah and colleagues investigated this in vivo [18] . First, two lines of transgenic mice that express DNMT3B7 were constructed and embryonic developmental effects were observed.…”
Section: Dnmt3b7 Expression Disrupts Embryonic Development and Accelementioning
confidence: 99%
“…First, two lines of transgenic mice that express DNMT3B7 were constructed and embryonic developmental effects were observed. Clear developmental abnormalities were noted including craniofacial, cardiac, and immune defects [18] . These results highlight the importance of proper methylation and subsequent gene silencing and activation during embryogenesis.…”
Section: Dnmt3b7 Expression Disrupts Embryonic Development and Accelementioning
confidence: 99%